Innovation Opportunities Analysis of Wadaw Moring MSME Using Value Proposition Design Approach - Prabandini, Alifia Dewi; Hasbi, Imannudin (Jambura Agribusiness Journal, 2024)
Wadaw Moring is a micro business sells Moring (Cimol Kering), a Sundanese snack made of starch. Since COVID-19, Wadaw Moring sales have not improved due to the company's weak value proposition. Therefore, this research was designed to find out what innovation opportunities can be carried out by Wadaw Moring as a value proposition. This research uses descriptive qualitative research methods with data collection techniques, including studying competitor publication documents and interviews using purposive sampling techniques. The research results show value proposition innovation for Wadaw Moring is applied as a popular West Java snack, that can be improved by combining local culture with contemporary art, using standardized procedures, and maintaining high spiciness levels. Packaging should be eye-catching, pricing should range between IDR 96.4 and IDR 100 per gram, stablish strategic partnerships with local stores, optimize online sales through discounts, and utilize advertising campaigns.